2008
DOI: 10.1152/ajprenal.90252.2008
|View full text |Cite
|
Sign up to set email alerts
|

Role of three-dimensional architecture in the urine concentrating mechanism of the rat renal inner medulla

Abstract: Recent studies of three-dimensional architecture of rat renal inner medulla (IM) and expression of membrane proteins associated with fluid and solute transport in nephrons and vasculature have revealed structural and transport properties that likely impact the IM urine concentrating mechanism. These studies have shown that 1) IM descending thin limbs (DTLs) have at least two or three functionally distinct subsegments; 2) most ascending thin limbs (ATLs) and about half the ascending vasa recta (AVR) are arrange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
81
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(84 citation statements)
references
References 76 publications
3
81
0
Order By: Relevance
“…The AQP1-positive DTLs lie predominantly within the vascular bundles alongside the UT-B-positive DVR (Fig. 9), in the vascular bundle regions that are spatially separate from regions occupied by CDs, in an ar- (40). Thus the close association of long-loop DTLs with CDs in the outer medulla undergoes an anatomic transition as DTLs descend from the outer medulla into and through the inner medulla, where they tend to lie distant from CDs.…”
Section: F630mentioning
confidence: 94%
See 1 more Smart Citation
“…The AQP1-positive DTLs lie predominantly within the vascular bundles alongside the UT-B-positive DVR (Fig. 9), in the vascular bundle regions that are spatially separate from regions occupied by CDs, in an ar- (40). Thus the close association of long-loop DTLs with CDs in the outer medulla undergoes an anatomic transition as DTLs descend from the outer medulla into and through the inner medulla, where they tend to lie distant from CDs.…”
Section: F630mentioning
confidence: 94%
“…Formation of both gradients reflects, in part, the tubulovascular architecture. The thin limbs of Henle, CDs, and blood vessels partition NaCl, urea, oxygen, water, and other molecules into and out of the multiple medullary compartments in a manner dependent upon their transepithelial or transendothelial permeability characteristics and gradients in addition to overall architecture (5,20,40). Consequently, the tubulovascular architecture can promote or constrain medullary countercurrent systems and other intercompartmental fluid, solute, and oxygen flows.…”
mentioning
confidence: 99%
“…UT-A4 is the N-terminal 25% of UT-A1 spliced to the C-terminal 25% (11). UT-B1 protein is expressed in red blood cells (11,16,17) and in nonfenestrated endothelial cells that are characteristic of descending vasa recta, especially in those that are external to collecting duct clusters (18).…”
Section: Urea Transportmentioning
confidence: 99%
“…countercurrent system; NaCl transport; urea transport; kidney DURING PERIODS OF WATER DEPRIVATION, the mammalian urine concentrating mechanism, which is localized in the renal medulla, stabilizes the osmolality of blood plasma by producing a urine that has an osmolality that substantially exceeds that of blood plasma. However, despite decades of sustained experimental and theoretical investigation (24,37,54,58), the nature of the urine concentrating mechanism in the inner medulla (IM) of the mammalian kidney remains controversial.Anatomic studies have revealed a highly structured organization of tubules and vasa recta in the outer medulla (OM) of some mammalian kidneys (2, 29), with tubules and vessels organized concentrically around vascular bundles, tightly packed clusters of parallel vessels, and tubules containing mostly vasa recta. Recent studies of the three-dimensional architecture of the rat IM and expression of membrane proteins associated with fluid and solute transport in nephrons and vasculature have revealed transport and structural properties that likely impact the IM urine concentrating mechanism in the rat kidney.…”
mentioning
confidence: 99%
“…countercurrent system; NaCl transport; urea transport; kidney DURING PERIODS OF WATER DEPRIVATION, the mammalian urine concentrating mechanism, which is localized in the renal medulla, stabilizes the osmolality of blood plasma by producing a urine that has an osmolality that substantially exceeds that of blood plasma. However, despite decades of sustained experimental and theoretical investigation (24,37,54,58), the nature of the urine concentrating mechanism in the inner medulla (IM) of the mammalian kidney remains controversial.…”
mentioning
confidence: 99%